2023
DOI: 10.3390/jcm12062123
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Adverse Effects of Mild COVID-19 Disease on Arterial Stiffness, and Systemic and Central Hemodynamics: A Pre-Post Study

Abstract: COVID-19-associated vascular disease complications are primarily associated with endothelial dysfunction; however, the consequences of disease on vascular structure and function, particularly in the long term (> 7 weeks post-infection), remain unexplored. Individual pre- and post-infection changes in arterial stiffness as well as central and systemic hemodynamic parameters were measured in patients diagnosed with mild COVID-19. As part of in-laboratory observational studies, baseline measurements were taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Another study demonstrated that at least 6 months after infection, COVID-19 survivors without other comorbidities associated with endothelial damage only showed mild evidence of endothelial dysfunction (41) . However, there were also studies indicating that the vascular damage became more severe with the progression of infection time (42) . Further investigation is warranted to explore the long-term effects of cardiovascular damage following COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that at least 6 months after infection, COVID-19 survivors without other comorbidities associated with endothelial damage only showed mild evidence of endothelial dysfunction (41) . However, there were also studies indicating that the vascular damage became more severe with the progression of infection time (42) . Further investigation is warranted to explore the long-term effects of cardiovascular damage following COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of new diabetes or hypertension among patients infected with SARS‐CoV‐2 compared with patients without infection, historical controls, or patients with a non–SARS‐CoV‐2 respiratory infection has been previously reported. 1 , 3 , 22 , 23 , 24 The higher risk of diabetes was seen even in patients with low preinfection risk of diabetes and may extend beyond the acute infection period, especially among those who develop symptoms of long COVID. 1 , 25 Given widespread undocumented COVID infection and long COVID in the population, it is relevant to quantify any increases in the population‐based rate of incident users of medications for diabetes or hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…This elevated risk of bypass/revascularization is probably a consequence of the higher incidence of ischemic heart disease in SARS-CoV-2 positive individuals. Other authors suggest that the increased occurrence of peripheral artery disease could be due to worsening arterial stiffness following SARS-CoV-2 infection [25] , [26] .…”
Section: Discussionmentioning
confidence: 99%